Managemet turnaround startegies: a case study of PIJ Autocare Sdn. Bhd. / Atan Ibrahim, Sahihad Mohd. Ali, Mohd. Helmi Mohd. Ali@Jaafar - Ibrahim, Atan; Mohd .Ali, Sahihad; Mohd. Ali@Jaafar, Mohd. Helmi (2012)
This study deals with Management Turnaround Strategies in recuperating an ailing of PIJ Autocare Sdn. Bhd. This case study suggests that in order to recover from failing to implement unique and distinguish management turnaround and objective of this study is to evaluate the causes of the underperforming specifically PIJ Autocare Sdn. Bhd. in terms of acceptable levels of profitability, liquidity and flow. The basis of Academic Construct is the basis foundation to be used in the study. In order to gain grounded information for this study, data were collected. In addition to elements that were analyzed, face to face interviews were conducted with various of people in the industry. Turnaround Plan is to determine the short term viability, longer term viability, turnaround strategy and a high level turnaround plan. __around strategy is described in terms of how the turnaround strategy components managing, stabilizing, funding and fixing an underperforming or distressed PIJ Autocare Sdn. Bhd. achieve its objectives turnaround plan and strategies must reverse causes of __ress, resolve the financial crisis, achieve a rapid improvement in financial perormance, regain stake holder support and overcome internal constraints and _avorable industry characteristics. Understanding all the above, the Group hope to be able to come up with a further recommendation study so that it can bring more value added to the industry in optimizing the operating and capital expenses based on the right dimensioning.